Tannin-containing legumes and forage diversity influence foraging behavior, diet digestibility, and nitrogen excretion by lambs - Lagrange, Sebastian Pablo; Villalba, Juan Jose (Oxford University Press, 2020)
Diverse combinations of forages with different nutrient profiles and plant secondary compounds may improve intake and nutrient utilization by ruminants. We tested the influence of diverse dietary combinations of tannin- (sainfoin-Onobrichis viciifolia; birdsfoot trefoil-Lotus corniculatus) and non-tannin- (alfalfa-Medicago sativa L.) containing legumes on intake and diet digestibility in lambs. Freshly cut birdsfoot trefoil, alfalfa, and sainfoin were offered in ad libitum amounts to 42 lambs in individual pens assigned to 7 treatments (6 animals/treatment): 1) single forage species (sainfoin [SF], birdsfoot trefoil [BFT], and alfalfa [ALF]), 2) all possible 2-way choices of the 3 forage species (alfalfa-sainfoin [ALF-SF], alfalfa-birdsfoot trefoil [ALF-BFT], and sainfoin-birdsfoot trefoil [SF-BFT]), or 3) a choice of all 3 forages (alfalfa-sainfoin-birdsfoot trefoil [ALF-SF-BFT]). Dry matter intake (DMI) was greater in ALF than in BFT (P = 0.002), and DMI in SF tended to be greater than in BFT (P = 0.053). However, when alfalfa was offered in a choice with either of the tannin-containing legumes (ALF-SF; ALF-BFT), DMI did not differ from ALF, whereas DMI in SF-BFT did not differ from SF (P > 0.10). When lambs were allowed to choose between 2 or 3 legume species, DMI was greater (36.6 vs. 33.2 g/kg BW; P = 0.038) or tended to be greater (37.4 vs. 33.2 g/kg BW; P = 0.067) than when lambs were fed single species, respectively. Intake did not differ between 2- or 3-way choice treatments (P = 0.723). Lambs preferred alfalfa over the tannin-containing legumes in a 70:30 ratio for 2-way choices, and alfalfa > sainfoin > birdsfoot trefoil in a 53:33:14 ratio for the 3-way choice. In vivo digestibility (DMD) was SF > BFT (72.0% vs. 67.7%; P = 0.012) and DMD in BFT tended to be greater than in ALF (64.6%; P = 0.061). Nevertheless, when alfalfa was offered in a choice with either sainfoin or birdsfoot trefoil (ALF-SF; ALF-BFT), DMD was greater than ALF (P < 0.001 and P = 0.007, respectively), suggesting positive associative effects. The SF treatment had lower blood urea nitrogen and greater fecal N/N intake ratios than the ALF, BFT, or ALF-BFT treatments (P < 0.05), implying a shift in the site of N excretion from urine to feces. In conclusion, offering diverse combinations of legumes to sheep enhanced intake and diet digestibility relative to feeding single species, while allowing for the incorporation of beneficial bioactive compounds like condensed tannins into the diet.